NILAI-NILAI PENDIDIKAN AKHLAK DALAM PERMAINAN TRADISIONAL BAREN - Teti Warohmah; Dede Darisman (Tarbiyat al-Aulad: Jurnal Pendidikan Islam Anak Usia Dini, 2018)
This research is motivated by the lack of role of parents and society in empowering traditional games, especially baren games. This is evidenced by the start of the extinction of various kinds of traditional children's games, while the fun method of educating one of them is with games. This study uses a qualitative field approach because researchers collect data by face to face and interact with people at the research site. After conducting research, the results obtained are the traditional game baren has its own benefits and has many values ​​of moral education, such as: love the environment and love for others, orderly and deliberate, patient, please help and be responsible. As for its implementation in daily life can not be separated from the exemplary and habits given by parents and educators. Because children learn more from parental examples, not commands, nagging, and even advice